Ultralow Lattice Thermal Conductivity and Large Glass‐Like Contribution in Cs3Bi2I6Cl3: Rattling Atoms and p‐Band Electrons Driven Dynamic Rotation - Yu Wu; Jialin Ji; Yimin Ding; Jiong Yang; Liujiang Zhou (Advanced Science)
Abstract Understanding the origin of ultralow lattice thermal conductivity κL of halide perovskites is of great significance in the energy conversion field. The soft phonon modes and the large anharmonicity corresponding to the dynamic rotation of halogen atoms play an important role in limiting the thermal transport of halide perovskites. The dynamic rotation has long been thought to originate from the electrostatic repulsion of lone pairs around halogen atoms. Here, by studying the layered perovskite Cs3Bi2I6Cl3, it is found that the interaction between the lone pairs contributed by the s bands of halogen atoms is short‐range, and the dynamic rotation is really driven by the occupied p‐band electrons. It dominates Cs3Bi2I6Cl3 with ultralow κL, < 0.2 W mK−1 at 300 K. Moreover, soft optical phonons are presented ≈1 and 2.2 THz that constitute relatively flat and dense bands due to the rattling Cs and Cl atoms, contributing a large glass‐like component to the κL. The results have important implications for understanding the origin of the ultralow κL in halide perovskites and for designing novel perovskites to serve the energy conversion field.